APLIKASI MEDIA SOSIAL UNTUK PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI ERA EKONOMI DIGITAL - Srirejeki, Kiky (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2016)
The purpose of this paper is to provide a description of the role and benefits of social media applications for micro, small and medium enterprises (SMEs). The research used mix-method, quantitative-qualitative methods to obtain data. Quantitative data obtained by questionnaire survey while the qualitative data obtained by in-depth interviews with owners or managers of SMEs as the respondents. The results of this study indicate that the majority of SMEs have used and take advantages of social media applications for their business. The perceived benefits of SMEs, among others is as a means of promoting products or services, expand access to new customers, facilitate business transactions with customers and suppliers as well as to increase sales. The research gives practical implication for improvement of the government policy to encourage the involvement of SMEs in the digital economy through infrastructure development and facilitate cheap service cost and Internet access, particularly in remote areas.Keywords: social media applications, SMEs.